Comparison of the effect of non-esterified and esterified astaxanthins on endurance performance in mice - Aoi, Wataru (J Clin Biochem Nutr, 2018)
Astaxanthin, a natural antioxidant, exists in non-esterified and esterified forms. Although it is known that astaxanthin can improve exercise endurance and cause metabolic improvement in skeletal muscle, the effects of the two different forms are unclear. We investigated the effects of the different forms of astaxanthin on endurance in mice. Eight-week-old ICR mice were divided into four groups: control; astaxanthin extracted from Haematococcus pluvialis in an esterified form; astaxanthin extracted from Phaffia rhodozyma in a non-esterified form; and astaxanthin synthesized chemically in a non-esterified form. After 5 weeks of treatment, each group was divided into sedentary and exercise groups. In the group fed astaxanthin from Haematococcus, the running time to exhaustion was longest, and the plasma and tissue concentrations of astaxanthin were significantly higher than those in the other groups. Astaxanthin from Haematococcus increased 5'-adenosine monophosphate-activated protein kinase levels in the skeletal muscle. Although the mice in the Haematococcus group ran for longer, hexanoyl lysine adduct levels in the skeletal muscle mitochondria were similar in the control and Haematococcus groups. Our results suggested that esterified astaxanthin promoted energy production and protected tissues from oxidative damage during exercise owing to its favorable absorption properties, leading to a longer running time.